2019
DOI: 10.5751/es-11036-240317
|View full text |Cite
|
Sign up to set email alerts
|

Context matters: horizontal and hierarchical network governance structures in Vietnam’s sanitation sector

Abstract: Governance networks describe the complex relations among different types of actors involved in the governance of a policy issue. Here, we ask how different institutional and socioeconomic contextual conditions influence the structure of these networks and result in more horizontal or hierarchical types of governance networks. To answer this question, we study Vietnam's sanitation sector and compare two different provinces, Hanoi and Ben Tre. More specifically, we analyze networks of information exchange among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…For recent applications of SNA on questions of governance in low-and middleincome countries, see e.g.,Brockhaus et al (2014),Andriamihaja et al (2019),Fischer et al (2019),Gorris et al (2019).4 In order to be consistent in terminology, for all the interviews, "small scale sanitation systems" were used to refer to decentralized STPs that serve between 10 and 1,000 households.…”
mentioning
confidence: 99%
“…For recent applications of SNA on questions of governance in low-and middleincome countries, see e.g.,Brockhaus et al (2014),Andriamihaja et al (2019),Fischer et al (2019),Gorris et al (2019).4 In order to be consistent in terminology, for all the interviews, "small scale sanitation systems" were used to refer to decentralized STPs that serve between 10 and 1,000 households.…”
mentioning
confidence: 99%
“…Although most of the articles deal with the difficulties of crossscale collaboration, two articles also included a discussion of challenges to collaboration within scales. Fischer et al (2019) investigated how different institutional histories affect the types of governance networks observed in the sanitation sector in two Vietnamese regions: the urban metropolis of Hanoi and the more rural province of Ben Tre. In Hanoi, local level actors have direct access to national level organizations, as well as donor organizations and other international actors, who typically promote horizontal forms of governance.…”
Section: Multiscale and Boundary-spanning Governance Challengesmentioning
confidence: 99%
“…Through their comparative analysis of sanitation management in Vietnam, Fischer et al (2019) illustrated how governance structures have, or have not, responded to policy changes in the sector. The authors discuss how socioeconomic and educational factors may help explain the observed differences in governance https://www.ecologyandsociety.org/vol24/iss3/art28/ structures between Hanoi and Ben Tre, as well as their implications for sanitation management in a setting in which the national government is seeking to decentralize administrative responsibilities while maintaining control over policy and investment.…”
Section: Diffuse Administrative Responsibilities: Institutional Challmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2016). On the other hand, the institutions and socio-political environment of many DCs can provide opportunities for a wider group of actors to interact, negotiate and cooperate (Fischer et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%